We need more than just male bodies in classrooms: Recruiting and retaining culturally relevant Black male teachers in early childhood education. Issue 3 (3rd July 2017) - Bryan, Nathaniel; Milton Williams, Toni
ABSTRACT: Nationwide, school districts struggle to recruit and retain Black males to the teaching profession. As a result, the presence of Black male teachers is lacking in public schools, which impacts the overall student outcomes for all children, particularly Black boys. Such recruitment and retention becomes even worse at the early childhood level, which explains the paucity of Black male teachers who are early childhood educators. To date, only 2% of teachers are Black males, of which most are middle and high school teachers. Furthermore, the clarion call for Black males to become teachers does not often prioritize Black male teachers who are culturally relevant. In this article, we focus on educational research regarding the lack of diversity of teachers and among males in K-12 to provide recommendations to the field of early childhood education, with specific attention to recruiting and retaining culturally relevant Black male teachers in early childhood education.